Pelaporan Yang Terintegrasi Di Rev. 4.0: Siapkah BUMN Di Indonesia? - Khalida Utami; Rafrini Amyulianthy; Tri Astuti (Jurnal Reviu Akuntansi dan Keuangan, 2022)
Integrated reporting has been proposed as a solution to the problem of misleading information in company reports, but its implementation has not been fully realized because regulations in each country regarding the implementation of corporate reporting in the form of IR are both mandatory and voluntary. The research proposes to assess Indonesia's readiness to apply IR among State-Owned Enterprises (SOE), and whether IR can be used as mandatory or voluntary disclosure. This study employs a quantitative approach that begins with data analysis on state-owned enterprises that issued annual reports on the Indonesia Stock Exchange. At a later stage, the overall score is calculated and evaluated with sensitivity analysis. The study finds the higher the amount of disclosure of firms implementing IR in Indonesia, the lesser the information gap obtained which can lead to a more effective corporate governance system This research has implications for companies in considering the application of integrated reporting in making decisions related to investments both in the short and long term, so that they can support the company's sustainable development strategy.